Transient startup characteristics of a drag-type hydrokinetic turbine rotor. (1st November 2020) - Zhao, Hexiang; Kang, Can; Ding, Kejing; Zhang, Yongchao; Li, Bing
Highlights: Startup process of a drag-type hydrokinetic turbine rotor was investigated. Flow-driven rotation of the rotor was modelled and implemented numerically. Flow characteristics during startup were described at three initial rotor positions. Startup failure as the initial static torque coefficient was positive was explained. Difference of flow pattern between dynamic and static states was demonstrated. Abstract: The present study aims to reveal startup characteristics of a drag-type rotor as it is used to harness kinetic energy of flowing water. The rotational speed of the rotor and the hydraulic loads exerted on the rotor were correlated. After being validated through experimental results, a numerical scheme was used to investigate instantaneous flow parameter distributions and the torque on the rotor during the startup process. Startup processes were analyzed at different initial azimuthal angles. The results show that a successful startup of the rotor is featured by two consecutive stages, an acceleration stage and a transition stage, which is then followed by periodic fluctuations of the angular velocity. The startup failure is proved at two initial azimuthal angles of 70° and 150°. The former one is associated with positive static torque coefficient. The two failed startup processes share similar rotation positions where the rotor eventually halts. During the startup process, instantaneous flow patterns differ significantly from those obtained in static state. Small torque coefficients lead to an overall attenuation of the rotational speed and are ascribed to uniform pressure distributions over each side of the blade surface.